Clinicopathologic Characterization of Oral Pyogenic Granuloma in 8 Cats. (June 2014) - Riehl, Jessica; Bell, Cynthia M.; Constantaras, Marika E.; Snyder, Christopher J.; Charlier, Cindy J.; Soukup, Jason W.
This case series characterizes the clinicopathologic features and treatment of oral pyogenic granuloma in 8 cats. The cats reported here were patients originating from collaborative efforts at an academic clinical teaching hospital and a specialty dentistry/oral surgery referral practice. Although the initial biopsy results were variable, in all cases the diagnosis reflected an inflammatory process. A second clinicopathologic evaluation of these cases determined that all lesions were consistent with oral pyogenic granuloma. The location of the lesion was consistent among all cats within the present study. Lesions developed at the vestibular mucogingival tissues of the mandibular first molar teeth. We propose that malocclusion and secondary traumatic contact of the ipsilateral maxillary fourth premolar tooth with the mandibular soft tissues is a possible contributing factor in the etiopathogenic mechanism.